Joaquim Jordà and Núria Villazán's Mones com la Becky [Monkeys Like Becky] (1999) and the New Global Disability Documentary Cinema - Fraser, Benjamin (Disability Studies Quarterly, 2019)
The documentary Mones com la Becky [Monkeys Like Becky] (1999) by Joaquim Jordà and Núria Villazán is a touchstone for global studies of the representation of cognitive difference. This challenging visual investigation into the violent international history of the lobotomy also foregrounds questions of theatrical and cinematic representation as they relate to cognition. Featuring dialogue in Catalan, Spanish, Portuguese, and English, Mones com la Becky uses a variety of formal strategies identified by theorist Bill Nichols to push beyond the limits of staid documentary filmmaking. This article makes the case that Jordà and Villazán's film should be seen as an early example of what David T. Mitchell and Sharon L. Snyder have called the "new disability documentary cinema."